New species of the genus Shelfordina Hebard with taxonomic and ecological notes and a key to the known Australian species (Blattodea: Ectobiidae: Pseudophyllodromiinae) - Rentz, David Cf; Field, Ashley Raymond; Su, You Ning (Zootaxa, 2024)
Three species in the ectobiid genus Shelfordina are highlighted with two described as new. The Orchid Cockroach, S. orchidae (Asahina) is included because of its occurrence in living orchid collections. A key to the known Australian species is included.